Programa etnomatemática e a cultura digital - Souza, Clécio Rodrigues de (2008)
The main aim of this study is to investigate the relationship between the computational practices (digital culture), which can be generated, organized and disseminated informally, and associate with the Ethnomathematics Program, being this relationship to Mathematics Education. To do this, we proposed the answer for the following question: What are, if they exist, the relationship between the Ethnomathematics and digital culture? . In order to answer that question, we build a theoretical framework based on D Ambrosio (1990, 2005), Costa (2003) and Gere (2002). First, a short course was designed, entitled: The link between Ethnomathematics and Informatics: a discussion about the investigation in the classroom involving teachers and students, raging from a variety of education background, in a major in mathematics. We had also a mixed questionnaire. Then, an interview was carried out (via e-mail) with one national and two international researchers. For reaching those goals, methodological procedures were taken in an educational qualitative approach